Child Penalties in Politics - Jon H. Fiva; Max-Emil M. King (Center for Economic Studies and ifo Institute (CESifo), 2022)
Women tend to experience substantial declines in their labor income after their first child is born, while men do not. Do such "child penalties" also exist in the political arena? Using extensive administrative data from Norway and an event-study methodology, we find that women drop out of local politics to a larger extent than men after their first child is born. Parenthood also seems to have a differential long-term effect on women and men's political careers, which may explain why women, especially women with children, are underrepresented at higher levels of the political hierarchy.
Keywords: D63; D72; J13; J16; 330; gender gap; child penalties; political selection